Modeling, Validation, and Performance of Two Tandem Cylinder Piezoelectric Energy Harvesters in Water Flow - Rujun Song; Chengwei Hou; Chongqiu Yang; Xianhai Yang; Qianjian Guo; Xiaobiao Shan (Micromachines, 2021)
This paper studies a novel enhanced energy-harvesting method to harvest water flow-induced vibration with a tandem arrangement of two piezoelectric energy harvesters (PEHs) in the direction of flowing water, through simulation modeling and experimental validation. A mathematical model is established by two individual-equivalent single-degree-of-freedom models, coupled with the hydrodynamic force obtained by computational fluid dynamics. Through the simulation analysis, the variation rules of vibration frequency, vibration amplitude, power generation and the distribution of flow field are obtained. And experimental tests are performed to verify the numerical calculation. The experimental and simulation results show that the upstream piezoelectric energy harvester (UPEH) is excited by the vortex-induced vibration, and the maximum value of performance is achieved when the UPEH and the vibration are resonant. As the vortex falls off from the UPEH, the downstream piezoelectric energy harvester (DPEH) generates a responsive beat frequency vibration. Energy-harvesting performance of the DPEH is better than that of the UPEH, especially at high speed flows. The maximum output power of the DPEH (371.7 μW) is 2.56 times of that of the UPEH (145.4 μW), at a specific spacing between the UPEN and the DPEH. Thereupon, the total output power of the two tandem piezoelectric energy harvester systems is significantly greater than that of the common single PEH, which provides a good foreground for further exploration of multiple piezoelectric energy harvesters system.